(untitled) (REGE Revista de Gestão, 2024)
Purpose: This article investigates the impact of teleworking, especially concerning work intensity, during the Covid-19 pandemic, on the routine of women university professors in Brazil. Method: The authors collected data through a web-based survey disseminated through social media and sent e-mails to professors (addresses obtained from educational institutions’ public information), reaching 1,471 responses which were analyzed by correlation and Multinomial Logistic Regression (MLR). Findings: We find evidence to confirm all hypotheses tested at different levels. The professors who noticed increased workload during the pandemic are mostly from private higher education institutions (HEIs). We also demonstrate the impact of professional and family contexts and find a higher number of negative feelings and workplace correlates that influence the perception of working more. Originality/value – This work problematizes the condition of women in Brazilian society, revealing the overload of work in the intersection between family, work, self-care, and other tasks. This study contributes to the literature exploring the home-office/telework in extreme periods, as is the case of the Covid-19 pandemic period.